Pediatric Biopharmaceutical Classification System: Using Age-Appropriate Initial Gastric Volume - Shawahna, Ramzi (AAPS J, 2016)
Development of optimized pediatric formulations for oral administration can be challenging, time consuming, and financially intensive process. Since its inception, the biopharmaceutical classification system (BCS) has facilitated the development of oral drug formulations destined for adults. At least theoretically, the BCS principles are applied also to pediatrics. A comprehensive age-appropriate BCS has not been fully developed. The objective of this work was to provisionally classify oral drugs listed on the latest World Health Organization’s Essential Medicines List for Children into an age-appropriate BCS. A total of 38 orally administered drugs were included in this classification. Dose numbers were calculated using age-appropriate initial gastric volume for neonates, 6-month-old infants, and children aging 1 year through adulthood. Using age-appropriate initial gastric volume and British National Formulary age-specific dosing recommendations in the calculation of dose numbers, the solubility classes shifted from low to high in pediatric subpopulations of 12 years and older for amoxicillin, 5 years, 12 years and older for cephalexin, 9 years and older for chloramphenicol, 3–4 years, 9–11 and 15 years and older for diazepam, 18 years and older (adult) for doxycycline and erythromycin, 8 years and older for phenobarbital, 10 years and older for prednisolone, and 15 years and older for trimethoprim. Pediatric biopharmaceutics are not fully understood where several knowledge gaps have been recently emphasized. The current biowaiver criteria are not suitable for safe application in all pediatric populations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1208/s12248-016-9885-2) contains supplementary material, which is available to authorized users.